2020
DOI: 10.1167/iovs.61.6.2
|View full text |Cite
|
Sign up to set email alerts
|

Tropomyosin 3.1 Association With Actin Stress Fibers is Required for Lens Epithelial to Mesenchymal Transition

Abstract: Epithelial to mesenchymal transition (EMT) is a cause of anterior and posterior subcapsular cataracts. Central to EMT is the formation of actin stress fibers. Selective targeting of actin stress fiber-associated tropomyosin (Tpm) in epithelial cells may be a means to prevent stress fiber formation and repress lens EMT. METHODS. We identified Tpm isoforms in mouse immortalized lens epithelial cells and epithelial and fiber cells from whole lenses by semi-quantitative reverse transcriptionpolymerase chain reacti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 56 publications
(81 reference statements)
4
37
1
Order By: Relevance
“…While generally a highly successful procedure, a large number of post-cataract surgery patients develop a fibrotic vision-impairing condition called Posterior Capsule Opacification (PCO) along the fiber cell-denuded region of posterior lens capsule [173]. At the cellular and molecular level, PCO is linked to the appearance of Collagen I-producing, αSMA+ myofibroblasts, of which one well-characterized source is the epithelial-mesenchymal transition (EMT) of lens epithelial cells [174][175][176][177][178][179][180][181][182][183][184][185][186][187][188]. The resident immune cells of the lens also have been identified as a progenitor source of αSMA+ myofibroblasts post-cataract surgery [165,189].…”
Section: Post-cataract Surgery Fibrosis -Posterior Capsule Opacification (Pco)mentioning
confidence: 99%
“…While generally a highly successful procedure, a large number of post-cataract surgery patients develop a fibrotic vision-impairing condition called Posterior Capsule Opacification (PCO) along the fiber cell-denuded region of posterior lens capsule [173]. At the cellular and molecular level, PCO is linked to the appearance of Collagen I-producing, αSMA+ myofibroblasts, of which one well-characterized source is the epithelial-mesenchymal transition (EMT) of lens epithelial cells [174][175][176][177][178][179][180][181][182][183][184][185][186][187][188]. The resident immune cells of the lens also have been identified as a progenitor source of αSMA+ myofibroblasts post-cataract surgery [165,189].…”
Section: Post-cataract Surgery Fibrosis -Posterior Capsule Opacification (Pco)mentioning
confidence: 99%
“…To identify novel actin filament interactions, we performed a proximity-dependent biotin identification (BioID) analysis (Roux et al, 2012) on human osteosarcoma cells (U2OS) using a biotin ligase fused to Tropomyosin-3.1 (Tpm3.1), a central actin filaments component (Supplementary Figure 1A; Parreno et al, 2020). Among the high-confidence interactors, CAV-1, which has been used as a measure of cytoplasmic trafficking of both individual and clustered forms of caveolae (Mundy et al, 2002;Echarri et al, 2012), was chosen for further investigation (Figure 1A).…”
Section: Cytoplasmic Cav-1 Interacts With Actin Filaments In Human Osteosarcoma Cellsmentioning
confidence: 99%
“…The lens epithelial cells continually proliferate and differentiate into fiber cells to support lens growth, a process that occurs throughout life. However, failure to maintain homeostasis in this anterior region of the lens could result in epithelial to mesenchymal transition (EMT) and pathologies, such as anterior subcapsular or posterior capsular opacification [1 , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] . Visualizing proteins in lens epithelial cells within intact lenses will help understand lens homeostasis as well as pathological processes.…”
Section: Methods Detailsmentioning
confidence: 99%
“…We demonstrated how tissue-scale mechanical loads are transmitted onto lens epithelial cells [15 , 16] ; moreover, others have demonstrated that whole lens stretch results in lens epithelial cell proliferation [16] . Furthermore, the ex vivo culture system has allowed for the study of lens EMT [4 , 5 , 7 , [17] , [18] , [19] . By culturing lenses in the presence of TGFβ, the lens EMT process (i.e., lens fibrosis) can be initiated and comprehensively examined.…”
Section: Methods Detailsmentioning
confidence: 99%